Exploring reciprocal interactions between groundwater and land cover decisions in flat agricultural areas and variable climate. (April 2020) - Zellner, Moira; García, Guillermo A.; Bert, Federico; Massey, Dean; Nosetto, Marcelo
Abstract: We present Hydroman, a flexible spatially explicit model coupling human and hydrological processes to explore shallow water tables and land cover interactions in flat agricultural landscapes, modeled after the Argentine Pampas. With fewer parameters, Hydroman aligned well with established hydrological models, and was validated with observed water table patterns and crop yield data. Simulations with different climate, phreatic and land cover conditions confirmed that climate remains the main driver, but crops also influence water levels and yields, depending on the growing cycle. We also examined the impacts of two alternative sowing strategies. Risk aversion proves robust in minimizing crop losses, but often results in less sowing, exacerbating flooding. Strict rotators risk more, but help stabilize the groundwater levels. Reintroducing pasture further stabilizes the system. Future work will engage farmers to derive and assess land cover strategies that maximize yield and minimize losses, and transfer our modeling approach to other applications. Highlights: We develop a valid, parsimonious, and flexible coupled human-natural system model. We model water table and land cover interactions in flat agricultural landscapes. Sowing decisions can influence water levels and yields over the long term. Adaptive land cover decisions may avoid crop losses, but exacerbate flooding. Flat agricultural areas should consider reintroducing pasture to stabilize the system.